Australia’s Digital Skills for Peace and War - Austin, Greg (Journal of Telecommunications and the Digital Economy, 2020)
This article gives an overview of Australia’s national military strategy for cyber space and the implied demands for a radical approach to development of our civil skills base. It then looks at developments in countries and groups of military interest to us in cyberspace. On this basis, the piece concludes with some recommendations for Australian policy.